Reversible Posterior Leukoencephalopathy in the Course of Goodpasture Syndrome - ELÇİOĞLU, ÖMER CELAL; OZKOK, Abdullah; Elcioglu, Omer Celal; BAKAN, Ali; ATILGAN, Kadir Gokhan; ALISIR, Sabahat; ODABAS, Ali Riza (My University, 2012)
Reversible posterior leukoencephalopathy syndrome (RPLS) is characterized by headache, altered consciousness, seizures, and cortical blindness. The most frequent etiological factors are hypertension, kidney diseases, and immunosuppressive drugs such as steroids and cyclophosphamide. Herein we present a case of a 22-year-old female patient presented with alveolar hemorrhage and acute renal failure necessitating hemodialysis. In renal biopsy, necrotizing crescentic glomerulonephritis and immunofluorescence pattern compatible with Goodpasture syndrome were found. Anti-glomerular basement membrane antibody result was positive. At follow-up, respiratory failure ensued, steroid pulse treatment was started, and she was transferred to intensive care unit (ICU). In the ICU, she had visual disturbances and blindness together with seizures. Cranial magnetic resonance imaging (MRI) revealed irregular T2- and fluid-attenuated inversion recovery (FLAIR)-weighted lesions in bilateral occipital lobes. On clinical and radiological grounds, RPLS was diagnosed. With the supportive and anti-hypertensive treatment, RPLS was resolved without a sequela. Subsequent cranial MRI was totally normal. In the literature, RPLS associated with Goodpasture syndrome was reported only once. Hypertension and methylprednisolone might be the responsible etiologies in this case.